Keefektifan Konseling Kelompok Rational Emotive Behavior Untuk Mengurangi Kecanduan Online Game Siswa SMP - Sholihah, Anna Nur (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2019)
This research is also aimed to find the effectiveness of Rational Emotive Behavior group counseling to reduce online game addiction among Junior High School students. This research used experiment method. The model was True Experiment Design. The research field was in SMP Negeri 1 Kutorejo  (Junior High School). Population of this research was 50 students.  Total sample of this research was 14 students. Average pretest score of experiment group is 76.71 with the minimum score is 73 and the maximum score is 80 while the average pretest score of experiment group is 42.43 with the minimum score is 34 and the maximum score is 64. Results of the research showed that there are significant differentiations between pre-test and post-test of experiment groups. Based on data analysis used Wilcoxon test obtained values on Asymp table, Sig, (2-tailed) is 0,018, which means that smaller than actual level (a/2=0,05) while the control group obtained values on Asymp table, Sig, (2-talied) is 0,915, which means bigger than the actual level (a/2=0,05).  refused and  acceoted. It means that Rational Emotive Behavior (REB) approach that is used in group counseling is effective to reduce online games addiction among junior high school students